The concomitance of splenic marginal zone lymphoma and sarcoidosis. A case description and review of the literature - Wiśniewska, Katarzyna; Lewandowski, Krzysztof; Olijarczyk, Tomasz; Komarnicki, Mieczysław (Contemporary Oncology/Współczesna Onkologia, 2009)
Splenic marginal zone lymphoma (SMZL) is an indolent lymphoproliferative disease, considered as a subtype of B-cell non-Hodgkin’s lymphoma (NHL) in the recent classification of haematological diseases, accounting for approximately 1% of all lymphomas. SMZL typically affects older patients and is extremely rare in patients younger than 30 years. The characteristic feature of SMZL is splenomegaly, often accompanied by circulating atypical “villous lymphocytes”. Histologically, the spleen in SMZL is characterised by a nodular infiltrate based on pre-existing white pulp but also involving the red pulp. Usually the splenic lymph nodes and bone marrow are also involved by a vaguely nodular infiltrate of similar nature. This case report concerns a 53-year-old patient suffering from SMZL, who was diagnosed with sarcoidosis simultaneously. An association between sarcoidosis and lymphopro-liferative diseases, the sarcoidosis-lymphoma syndrome, has been previously described, but to our knowledge this is the first publication concerning coexistence of sarcoidosis with SMZL.